Association of social capital and adherence to a Mediterranean diet in adults living in Tehran: a cross-sectional study - Reyhane Norouziasl; Sakineh Shab-Bidar (BMC, 2024)
Abstract Background Understanding the role of social capital in adherence to the Mediterranean diet can inform interventions to promote healthier eating habits in Iranian adults. Methods This was a cross-sectional study. Dietary intake was assessed using a 168-item semi-quantitative food frequency questionnaire. Adherence to the Mediterranean diet was measured by the Mediterranean diet score (MDS), ranging from 0 to 18. The Social Capital Questionnaire (SCQ), in which questions are scored on a 4-point Likert scale from "never" (= 1) to "always" (= 4), was used. Linear regression controlling for sex, age, marital status, BMI, education, lifestyle and chronic diseases (diabetes, hypertension, dyslipidemia and cardiovascular diseases) and energy intake was used to calculate unstandardized coefficients (B) and 95% CIs. A total of 270 adults with a mean age of 36.76 ± 13.22 years who lived in Tehran were enrolled. Results 270 adults (118 males and 152 females) were included. Multivariate-adjusted B showed a positive association between social capital and adherence to a Mediterranean diet (β ± SE = 0.54 ± 0.15, 95% CI = 0.24, 0.84 P = 0.001). Adding energy intake as a new covariate in Model 3 was not accompanied by an enormous change (β ± SE = 0.55 ± 0.15, 95% CI = 0.24, 0.85 P ˂0.001). Conclusion This cross-sectional study indicated that better social capital in adults is significantly associated with greater adherence to a Mediterranean diet. We suggest that future studies investigate this association in larger sample sizes.